Effect of micro-vacuum storage on active oxygen metabolism, internal browning and related enzyme activities in Laiyang pear (Pyrus bretschneideri Reld). (October 2016) - Fan, Mingcong; Li, Wenxiang; Hu, Xinlei; Sun, Ya'nan; Yu, Ge; Zhang, Xin
Abstract: To investigate the effects of micro-vacuum (MV) storage on Laiyang pear fruit senescence, freshly harvested Laiyang pears ( Pyrus bretschneideri Reld) were subjected to MV storage (70 ± 5 kPa) and atmospheric pressure storage at 3 ± 1 °C for 120 days. MV storage was found to be more effective in maintaining post-harvest Laiyang pear quality, preventing increased respiration and decreased firmness and inhibiting internal browning. Furthermore, MV storage reduced the rate of O2 − production and the accumulation of H2 O2 and malondialdehyde (MDA), and maintained significantly higher activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD), although the activities of lipoxygenase (LOX) and polyphenol oxidase (PPO) were inhibited. These results indicate that the delay in senescence and ripening of Laiyang pears stored under MV is conditions due to inhibition of respiration and maintenance of higher antioxidant enzymes activity (SOD, CAT, POD), leading to reduced reactive oxygen species (ROS) accumulation, lower PPO activity and better cell membrane integrity. Highlights: A micro-vacuum (MV) equipment was designed and applied for the storage of Laiyang Pears. Pears' respiratory rate and internal browning was inhibited in MV condition. MV condition is more effective in inhibiting accumulation of pears' ROS. Pears' antioxidant enzyme activities were significantly maintained. MV condition showed promise as a maintainer for fruits senescence and harvested quality.